Comparative study on insured and uninsured patients' perceptions on responsiveness of inpatient services of Tertiary healthcare facility of Nepal. - Oli,Pratibha (2020)
ABSTRACT: The responsiveness of a health system is considered to be an intrinsic goal of health systems and an essential aspect in performance assessment. This brought into highlight the non medical aspects of patients depend upon how health care facilities acknowledges patient's demand. Responsiveness concentrates on the different type of interaction that people have within the system. Higher responsiveness is found to contribute for higher chances of treatment successes. Present heath system in developing as well as developed countries are experiencing growing expectations from demand side. Developed health systems have been working on assessment of performance of health care systems where less developed systems are still focusing on health care delivery with little attention given to patients' experience while improvements in responsiveness are expected to increase health seeking behavior of patients. Responsiveness has received little attention in low and middle income countries while it has been used as performance indicator in developed countries. The aim of study is to assess insured and uninsured patients' perceptions of responsiveness of inpatient services of tertiary hospital of Kathmandu Nepal. The study design was cross-sectional and hospital based which follow the quantitative method. National Academy of Medical sciences, Bir hospital was taken and total of 228 (114 for insured patients and 114 for uninsured patients) participants were taken using simple random sampling. Ethical approval was taken from IRB of Institute of Medicine and Nepal Health Research Council. The data was collected through face to face interview technique, was entered in EpiData 3.1 and SPSS version 21 was used for analysis. Bivariate and Multivariate logistic regression was used to find the association between dependent and independent variables. The mean age of overall patients was 46.63 years with standard deviation (SD) of 16.33 years. A higher proportion was male in both groups. The findings show high majority of patients had poor perceived health status. Majority of patients (74.1%) responded that enough medicines were not available within the hospital pharmacy. Prompt attention and clarity of communication were considered extremely important by overall patients. Poor experience was reported for prompt attention, clarity of communication, choice of service provider and quality of basic amenities by both insured and uninsured groups of patients. Socio demographic variable were not found to be significantly associated with perceived responsiveness among insured and uninsured patients. Inpatients information like got services as expected, availability of enough medicine within hospital pharmacy, duration of stay in both group and satisfied with insurance were found to be significantly associated with perceived responsiveness among insured patients. Priority areas for action to improve responsiveness of patients are prompt attention, clarity of communication, quality of surroundings. Decreased waiting time at hospitals, increased availability of medicine, and improved quality of services could improve the responsiveness of inpatient's services of tertiary hospital.